Sleep Patterns Among Athletes and Non-Athletes During Ramadan intermittent fasting: Systematic Review, Meta‑Analysis and Meta‑Regression - El-Jaziz, Anas; Lotfi, Said (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Ramadan fasting is a religious observance practiced regularly by Muslims and may have an effect on sleep quality, especially for athletes. Our systematic review with meta-analysis aims to identify the effect of Ramadan observance on the sleep patterns of athletes and non-athletes during Ramadan fasting over the teen years (2014-2024). Study design. A systematic search of Scopus, Web of Science, and Pubmed, was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-analyses. Methods. After a deep search in the three databases, we downloaded all the references that respected our request. all the references were imported into the COVIDENCE platform. Two independent researchers were designated to look for the criteria inclusion and to appraise each study. A third reviewer resolved conflicts if there is a divergence of judgment. Then, we obtained an Excel file that compiles all the data collected. The meta-analysis and meta-regression were compilated. Results. 345 documents were found. Of these, 14 respected all the criteria. Our findings revealed that while sleep latency and di- sturbance remained unaffected by Ramadan, sleep duration and efficiency were negatively impacted, particularly among amateur athletes. Interestingly, the overall sleep quality, daytime dysfunction, and subjective sleep quality showed a positive impact from Ramadan, which was more evident among amateur athletes. Conclusions. In the context of Ramadan fasting, these results suggest that Ramadan has a negative impact on the sleep patterns of athletes and non-athletes.